Penggunaan Kerangka Kerja COBIT 4.1 Sebagai Hasil Evaluasi Pengelolaan Teknologi Informasi CV. INDOJAYA - Wishnu Aribowo Probonegoro; Lili Indah Sari; parlia romadiana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The role, influence and use of information technology today impacts all companies, including CV Indojaya. CV. INDOJAYA is a retread tire manufacturing company as well as a distributor to various areas in the province of Bangka Belitung. The use of information technology has the potential to determine success, success, to gain a competitive advantage for the company. Increased use of information technology must be directly proportional to the investment that has been issued. For this reason, it is necessary to have good information technology governance, by evaluating the use of IT governance. In order for the investment in Information Technology that has been issued by CV Indojaya to be comparable to the objectives, CV Indojaya must implement good Information Technology Governance. Currently CV Indojaya has used and implemented the management of information technology, but there has never been an evaluation of the management of existing information technology. Therefore, it is necessary to evaluate the management of information technology using the COBIT 4.1 framework. Because COBIT (Control Objective for Information and Related Technology) has an information technology framework and provides guidance based on best practices according to ISACA to managers, auditors, users to bridge business aspects, IT control and technical needs. The results of this study using the measurement of maturity level, that CV Indojaya is currently still at level 2, namely Repeatable level,